Modeling and Simulation of the Intrinsic Function of a Photonic Switch - Lydiate, Joseph (Frontiers in Physics, 2018)
In this paper, I provide modeling and simulation results which show that a photonic switch can be realized by the application of two superluminescent light emitting diodes to a configuration of three 10 μm radius micro-ring resonators. The 130 nm silicon on insulator rib structure is adopted for the simulations. The three 10 μm radius rings have a resonant wavelength of 1.5487 μm. The on or off state, at a single output port, is realized by the application of a superluminescent diode at either, one or the other, of the two input ports. The output intensity, at the ring resonant wavelength, is shown as a single normalized peak representing a 1 or the “on” condition. The single peak is realized by the application of the “on” superluminescent diode. The “off” or the 0 condition, realized by the application of the “off” superluminescent diode, is exhibited at the output by the introduction of an optical transparency at the single peak resonant wavelength. The minimum of the optical transparency can be adjusted by changing the coupling gap distances of the design. The transparency minimum introduces an error detection feature whereby a failure of the “off” excitation superluminescent diode results in a zero or noise floor output. The transparency minimum can be increased to raise the off state minimum above the measurement apparatus noise floor. The output of the switch can be detected using a simple photodiode intensity detection method.